Analysis of copy number variation at DMBT1 and age-related macular degeneration. Issue 1 (December 2016) - Polley, Shamik; Cipriani, Valentina; Khan, Jane; Shahid, Humma; Moore, Anthony; Yates, John; Hollox, Edward
Abstract Background DMBT1 is a gene that shows extensive copy number variation (CNV) that alters the number of bacteria-binding domains in the protein and has been shown to activate the complement pathway. It lies next to theARMS2 /HTRA1 genes in a region of chromosome 10q26, where single nucleotide variants have been strongly associated with age-related macular degeneration (AMD), the commonest cause of blindness in Western populations. Complement activation is thought to be a key factor in the pathogenesis of this condition. We sought to investigate whether DMBT1 CNV plays any role in the susceptibility to AMD. Methods We analysed long-range linkage disequilibrium ofDMBT1 CNV1 and CNV2 with flanking single nucleotide polymorphisms (SNPs) using our previously published CNV and HapMap Phase 3 SNP data in the CEPH Europeans from Utah (CEU). We then typed a large cohort of 860 AMD patients and 419 examined age-matched controls for copy number atDMBT1 CNV1 and CNV2 and combined these data with copy numbers from a further 480 unexamined controls. Results We found weak linkage disequilibrium betweenDMBT1 CNV1 and CNV2 with the SNPs rs1474526 and rs714816 in theHTRA1 /ARMS2 region. By directly analysing copy number variation, we found no evidence of association of CNV1 or CNV2 with AMD. Conclusions We have shown that copy number variation atDMBT1 does not affect risk of developing age-related macular degeneration and can therefore be ruled out from future studies investigating the association of structural variation at 10q26 with AMD.